Aluminum-induced ultraweak luminescence changes in root-tip cells of barley - HU Xian-ming; PAN Jian-wei; CHEN Hong; ZHU Mu-yuan (浙江大学学报. 农业与生命科学版)
Ultraweak luminescence (UL) analysis technology plays an important role in plant researches (such as plant growth, development, senescence, death, disease-resistance, and stress-resistance against adverse environment). UL changes of root-tips in different aluminum-resistant barley cultivars were examined under aluminum stress in this study. Our data revealed that roots of two barley cultivars that differed in their aluminum resistance gave different UL curves during normal seed germination. UL values of root-tips in four barley cultivars under aluminum stress ranked as follows: Humai 8≫Zhepi 2>Zhaoshu 3>Shengxian six-rows. This order was consistent with the ranking of their aluminum-resistance as assessed by root growth rates. These results prove that UL analysis technology is valuable as a method for assessment of aluminum-resistance in barley.